To solve for the unknown angle measures, we know that the angles between the three rays should sum up to 90 degrees since the first ray (vertical) and the third ray (horizontal) form a right angle.
The angle between the first and second rays is labeled as \( (x+4)^\circ \) and the angle between the second and third rays is labeled as \( (3x+2)^\circ \).
We can express the relationship as:
\[ (x + 4) + (3x + 2) = 90 \]
Now, let's simplify the equation:
\[ x + 4 + 3x + 2 = 90 \]
Combining like terms gives us:
\[ 4x + 6 = 90 \]
Next, we isolate \(4x\) by subtracting 6 from both sides:
\[ 4x = 90 - 6 \] \[ 4x = 84 \]
Now, divide by 4:
\[ x = 21 \]
Now we can calculate the two unknown angle measures:
-
For the angle \( (x + 4)^\circ \): \[ (x + 4) = 21 + 4 = 25^\circ \]
-
For the angle \( (3x + 2)^\circ \): \[ (3x + 2) = 3(21) + 2 = 63 + 2 = 65^\circ \]
Thus, the two unknown angle measures that form the 90° angle are:
\[ (x+4)^\circ = 25^\circ, \quad (3x+2)^\circ = 65^\circ \]